The contribution of teacher structure, involvement, and autonomy support on student engagement in low-income elementary schools. Issue 5 (17th August 2020) - Archambault, Isabelle; Pascal, Sophie; Tardif-Grenier, Kristel; Dupéré, Véronique; Janosz, Michel; Parent, Sophie; Pagani, Linda. S
ABSTRACT: Providing high-quality teaching practices is central to promote student engagement in school. High quality teaching is even more important in schools located in low socioeconomic neighborhoods, where a larger proportion of children present more important academic difficulties and lower classroom behavioural, affective, and cognitive engagement. The Self-System Model of Motivational Development posits that learner engagement is favored when teachers structure classroom activity, are involved with students, and support their autonomy. How these dimensions interact to create effective classroom contexts that foster student engagement remains less documented. The goal of the present study was to test additive and combined (interactive) multilevel longitudinal associations between teacher structure, autonomy-support, and involvement on students behavioral, affective, and cognitive engagement across one school year. Based on a sample of 696 low SES elementary school students, results of our path analysis revealed that teacher involvement and autonomy-support contributed to various dimensions of classroom engagement. Besides, structure was not directly to this outcome. Yet, a combined use of autonomy-support and structure or autonomy-support and involvement was associated with higher behavioral engagement among low-SES children. These results suggest that teacher practices cannot be interpreted in isolation as they add up and interact to contribute to elementary school student academic experience.